2009
DOI: 10.1158/0008-5472.can-09-0551
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Inactivation of the Circadian Clock Gene BMAL1 in Hematologic Malignancies

Abstract: Disruption of circadian rhythms, daily oscillations in biological processes that are regulated by an endogenous clock, has been linked to tumorigenesis. Normal and malignant tissues often show asynchronies in cell proliferation and metabolic rhythms. Cancer chronotherapy takes biological time into account to improve the therapy. However, alterations of the circadian clock machinery genes have rarely been reported in human cancer. Herein, we show that the BMAL1 gene, a core component of the circadian clock, is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
120
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(131 citation statements)
references
References 30 publications
5
120
0
6
Order By: Relevance
“…Bmal1 was suggested to be a positive regulator of tumor growth and metastasis, acting by expressing vascular endothelial growth factor in cancer (27). Bmal1 epigenetic inactivation contributes to the development of hematologic malignancies by disrupting the cellular circadian clock (28). per1 inactivation is thought to play an important role in carcinogenesis (29).…”
Section: Discussionmentioning
confidence: 99%
“…Bmal1 was suggested to be a positive regulator of tumor growth and metastasis, acting by expressing vascular endothelial growth factor in cancer (27). Bmal1 epigenetic inactivation contributes to the development of hematologic malignancies by disrupting the cellular circadian clock (28). per1 inactivation is thought to play an important role in carcinogenesis (29).…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson (Lin et al, 2012), whereas DNA hypermethylation-associated loss of BMAL1, which has been reported in leukemia/lymphoma cells, prevents the recruitment of its natural partner, CLOCK, to their common targets, further enhancing the perturbed circadian rhythm of the cancer cells (Taniguchi et al, 2009). Very importantly, a maternal diet rich in fat modulates in utero the acetylation of fetal histone H3 at lysine 14 (H3K14ac) in NPAS2, a paralog of the CLOCK transcription factor, affecting thus the peripheral circadian system of the fetus .…”
Section: Circadian Rhythms and Sleepmentioning
confidence: 96%
“…Deregulated expression of the PER1, PER2 and PER3 genes as well as inactivation or knockout PER1, PER2, CLOCK and BMAL1 leads to malignization, especially in the breast, as well as to the appearance of different disorders such as obesity [22][23][24][25]. In the regulation of circadian clock system casein kinases play an important role, especially casein kinase-1ε (CSNK1E) and -1δ (CSNK1D) [26][27][28].…”
Section: Introductionmentioning
confidence: 99%